A relação verbo-visual do texto multimodal em tela da criança em aquisição de escrita e em processo de letramento digital. - Silva, Gisely Martins da (2017)
This research aims to analyze the contributions of digital literacy to the multimodal acquisition of a child's writing from instant messages in the applications: Facebook Messenger and WhatsApp Messenger. It is a case study of a qualitative and longitudinal nature because it is the analysis of the verbal-visual relation of the multimodal writing of a child in the literacy cycle. The relation between image and verbal text was analyzed from screens captured in the applications mentioned and provided by the child's father. In order to verify the relation of status and meaning between image and verbal text, we select the verbal-visual relation of superiority, equality and inferiority presented by Martinec and Salway (2005) and Fonte e Caiado (2014, 2015), we are also supported by collaborations of Santaella (2002) to carry out the analyzes. Concerning digital literacy, our research is supported by the postulates of Xavier (2002) and Soares (2002), and about the studies on multimodality we rely on Kress (2003), Van Leeuwen (2011), Kress and Van Leeuwen (2006 [ 1996]; [2001]) and Dionysus (2006). To reach our objective, we selected twelve screen captures with the presence of the multimodal text of the child in the literacy cycle. We observed how the child uses the multimodal resources in the years of the literacy cycle and what emojis’ roles used in the multimodal texts posted in Facebook Messenger and WhatsApp Messenger. We also observed that during the digital literacy process the child expanded the repertoire of multimodal resources. We realized that the child has developed varied actions in the process of digital literacy, in which it is still found. At the beginning of this process, the child using multimodal resources, the verbal-visual relation status prevailing was inferiority or superiority of one of the resources - written or imagery - and, as the child came to know the possibilities of writing Multimodal and improving itself digitally, the relation of verbal-visual sense became more complementary. We believe that our study, faced with the challenges posed by digital culture, involving differentiated practices of reading and writing on screen, becomes relevant when we discuss the multimodality linked to mobile digital technology and we reflect on the verbal-visual interrelation in discursive practices of a child in the literacy cycle, which occurred in Facebook Messenger and WhatsApp Messenger.